2020
DOI: 10.1111/jonm.13010
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ work characteristics and self‐assessment of the work environment—Explorative cross‐sectional study

Abstract: Aim The aim of the study was to explore the characteristics of nursing work and the correlation with the conditions in nurses’ work environment. Background Although the correlation between nurses’ work characteristics and the safety of health care provision has been confirmed, nurses continue to work in discouraging environments. Method A cross‐sectional study was conducted. A total of 1,744 nurses from 16 Slovenian hospitals participated. Variables included the following: work characteristics, ergonomic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…Nurses in general typically perform their patient related work tasks in a standing position [16]. This also applies to nurses in the haemodialysis setting.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses in general typically perform their patient related work tasks in a standing position [16]. This also applies to nurses in the haemodialysis setting.…”
Section: Discussionmentioning
confidence: 99%
“…According to Saleh et al (2020), the majority of head nurses of clinical units are male, and participants stated that male nurses have more management skills. In addition, Skela‐Savič et al (2020) stated that male nurses display more effective decision‐making authority and leadership skills. According to these findings, the gender of nurse managers affects management skills and styles.…”
Section: Discussionmentioning
confidence: 99%
“…In his concept analysis of male nurses, Sasa (2019) found that being a male nurse influenced the units in which male nurses worked, level of job satisfaction, collegial relationships, promotion opportunities and societal perspectives concerning the nursing profession. Studies have found that gender role expectations also affect nurses' management and leadership skills, and most studies concur that society assigns leadership roles to men because it is believed that male nurses have better leadership and management skills (Alghamdi et al, 2018; Saleh et al, 2020; Skela‐Savič et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This outcome could be explained by the fact that nurses who have completed a master's degree have acquired a set of competencies that give them a sense of greater control and decision‐making capacity in their clinical practice, as well as greater use of their skills. In this sense, several studies indicate that nurses with higher educational levels have better work abilities than their colleagues with lower educational levels (van Doorn et al., 2016; Skela‐Savič et al., 2020; Svavarsdottir et al., 2018). Similarly, the theoretical foundations of the JDCS model indicate that control over the work process can be facilitated through greater learning (Karasek & Theorell, 1990).…”
Section: Discussionmentioning
confidence: 99%